Periodic Variations in the Wavelength Distributions following Photon Interferences: Analogy with Electron Interferences - Vabre, Maxime (2012)
A new interference phenomenon is reported, which has so far not been observed with either matter or light. In a nanometer-sized version of Feynman’s famous two-slit “thought” experiment with single electrons, the width of a quasi-monochromatic line has been found to oscillate with the detection angle. Since this experiment resembles the original double-slit experiment by Young with light (1807), photon interferences were investigated in order to determine the wavelength distribution as a function of the position in the interference field. In addition to the well-known oscillating dependence of the intensity with a succession of dark and bright fringes, a periodic dependence with respect to the detection position has also been observed for the width of the wavelength distribution, revealing a larger analogy between electron and photon interferences.